A case report of multi-system inflammatory syndrome in adults (MIS-A) associated with heart failure. Issue 10 (1st October 2021) - Mittal, Nitish; Abohelwa, Mostafa; Brogan, Joshua; Nichols, Jacob
Abstract: Background: Multi-system inflammatory syndrome in children (MIS-C) is a systemic inflammatory condition where various body organs, such as the heart, kidney, gastrointestinal organs, become inflamed. Several cases have been reported in children linking MIS-C with novel corona virus disease-2019 (COVID-19); however, few cases have been reported in adults [multi-system inflammatory syndrome in adults (MIS-A)]. Case summary: A case of a 20-year-old male patient with a history of COVID-19 infection 2 months before presentation who presented with fever and acute right lower quadrant pain. Workup revealed right-sided mesenteric lymphadenopathy and mild colitis that was non-responsive to antibiotics. The patient was found to have significantly elevated inflammatory markers. He also developed myocarditis resulting in acute systolic heart failure with reduced ejection fraction. The diagnosis of MIS-A was made by exclusion. The patient showed improvement with intravenous immunoglobulin and pulse steroids. Based on the available literature, MIS-C was defined till the age of 21; however, we think it is a misnomer for adults more than 18. Hence, we prefer to use MIS-A for our patient. Conclusion: It is essential to diagnose and treat patients with the multi-system inflammatory syndrome at an early stage; the management of these patients, especially with heart disease, should include immune-modulatory therapy as well as guideline-directed therapy.